Chemically Orthogonal Three‐Patch Microparticles1. Issue 9 (14th February 2014) - Rahmani, Sahar; Saha, Sampa; Durmaz, Hakan; Donini, Alessandro; Misra, Asish C; Yoon, Jaewon; Lahann, Joerg
Abstract Compared to two‐dimensional substrates, only a few methodologies exist for the spatially controlled decoration of three‐dimensional objects, such as microparticles. Combining electrohydrodynamic co‐jetting with synthetic polymer chemistry, we were able to create two‐ and three‐patch microparticles displaying chemically orthogonal anchor groups on three distinct surface patches of the same particle. This approach takes advantage of a combination of novel chemically orthogonal polylactide‐based polymers and their processing by electrohydrodynamic co‐jetting to yield unprecedented multifunctional microparticles. Several micropatterned particles were fabricated displaying orthogonal click functionalities. Specifically, we demonstrate novel two‐ and three‐patch particles. Multi‐patch particles are highly sought after for their potential to present multiple distinct ligands in a directional manner. This work clearly establishes a viable route towards orthogonal reaction strategies on multivalent micropatterned particles.